KANDUNGAN Escherichia coli PADA DAGING BROILER DI PASAR-PASAR TRADISIONAL KABUPATEN TANGGAMUS - Safitri, Leni; Santosa, Purnama Edy; Suharyati, Sri (Jurnal Riset dan Inovasi Peternakan, 2017)
This research that conducted in December 2016 – January 2017 intended to determine the content of Eschericia coli in broiler meat from traditional markets of Tanggamus district. The analysis of E.coli content was done in laboratory of veterinary public health, Regional Veterinary Hall III Lampung.  This research used 28 samples that collected by random sampling in the morning and daylight.  The obtained data were made in tabulation form and  analyzed descriptively to the sample condition that collected in the morning and daylight.  The results of this research indicated that from the total of 28 sample, came from 4 markets with 19 traders, there were 25 meat samples contained amount of E.coli below the standard and 3 samples contained the E.coli above the standard.  The three samples that exceeding the standard were consisted of 1 sample belonged to Liliana, merchant from Gisting Market, with the daylight collecting-time and 2 samples belonged to Abu Yusuf and Agus, merchant from Kota Agung market,with the morning collecting-time.        Key Words: Broiler, Escherichia coli, Traditional Market, Tanggamus